LEGAL PROTECTION FOR VICTIMS OF ADULTERY - Budi Suhariyanto (Pusbindiklat - LIPI, 2012)
Adultery set in the KUHP has a weakness in defining act of adultery which is different from the living law.There are individual victims and community who have no legal protection. Therefore, legal protection for victimsof adultery is necessary. This research is a normative legal research with normative juridical approach. The dataused are secondary data which were analyzed using qualitative methods of juridical analysis. The results of thisstudy concluded that legal protection for victims of adultery can be done through legal discovery by a judge orthrough criminalization policy accommodating the living law.Keywords: Protection, Victims, Adultery.